A study on the assessment of Iran’s designed, developed and implemented elementary school Farsi curriculum based on holistic criteria in teaching language arts - Nāder salsabili (فصلنامه نوآوری‌های آموزشی, 2010)
In this research, we analyzed and assessed Iran’s elementary school Farsi curriculum (Bekhanim-Benvisim) at three stages of designed, developed and implemented curriculum based on holistic approach in curriculum and language arts instruction. The research has been done at 4 stages: 1) Through emphasis on holistic approach in language arts instruction through investigating the theoretical foundation and related literature on language arts education, the criteria were determined. Also, the designed elementary school Farsi curriculum was primarily identified. 2) based on two categories of criteria (taken from theoretical foundation of holistic approach and the criteria taken from the designed elementary school Farsi curriculum) the designed curriculum and the developed content was described and assessed. 3) the implemented curriculum was assessed at two phases (second to fifth elementary grade) and 4 phases of observation of 24 classes of sample (3 educational districts of Tehran, 3 girl schools and 3 boy schools at each educational district), with 6 clasess at each grade (second to fifth grade) and 186 to 206 students from each grade. 4) through comparing, analyzing and interpreting the findings obtained from the assessment of elementary school Farsi curriculum, the changes and shortcomings of the curriculum and the required revisions was suggested. The findings indicated the limited attention to holistic approach and the criteria for the designed elementary school Farsi curriculum. It became clear that the concept of holistic approach in the developed curriculum and textbooks is a limited one. Considering the existing methodological and instructional limitations, the instructions during the academic year do no have a remarkable influence on enhancing the students’ holistic view. The detailed findings of this paper present an almost exact picture of shortcomings of the existing curriculum and instructions.